The Influence of Communication, Work Conflict and Work Discipline on Employee Performance at PT Galuh Buana Sukses - Asiang Asiang; Mauli Siagian (LPPM Universitas Buddhi Dharma, 2025)
In the world of organizations and companies, employee performance is one of the key factors that determines the success of an entity. Employee performance is an effort that has been made by employees in carrying out the duties assigned based on their abilities and experience in completing their tasks. PT Galuh Buana Sukses is a company that provides heavy equipment rental and repair services, as for the heavy equipment rented by this company such as forklifts and cranes. Apart from being a service provider, PT Galuh Buana Sukses is also experienced in working on logistical support, construction support, oil & gas support and others. PT Galuh Buana Sukses experienced internal problems related to communication, work conflicts, and work discipline that had an effect on the performance of its employees. The purpose of this study is to find out whether there is an influence of communication, work conflict and work discipline on employee performance at PT Galuh Buana Sukses both partially and simultaneously. This study uses quantitative research with saturated sampling techniques. The results of this study are that there is a positive and significant influence of communication on employee performance. There is a positive and significant effect of work conflict on employee performance. There is a positive and significant influence of work discipline on employee performance. There is a simultaneous or simultaneous influence between communication, work conflicts and work discipline on employee performance at PT Galuh Buana Sukses.